Synthesis, crystal structure, and photodegradation properties of a new multicore Zn(II) metal organic framework. Issue 12 (2nd December 2019) - Yu, Yifan; Zong, Ziao; Fan, Chuanbin; Meng, Xiangmin; Zhang, Xia; Fan, Yuhua
Abstract: A novel metal organic framework, namely, {[Zn3 (btc)2 (bimmb)2.5 ]·2H2 O·CH3 CN} n (1 ) (btc = 1, 3, 5-benzenetricarboxylic acid), bimmb = 1, 4-bis(imidazol-l-ylmethyl) benzene), has been reasonably designed, successfully solvothermally synthesized, and characterized. The complex is characterized by elemental analysis, IR spectroscopy, single-crystal X-ray diffraction, thermogravimetric analysis, and powder X-ray diffraction. Complex1 exhibits a 5-nodal 3, 3, 4, 4, 6-connected 3D framework with a (5·6·7)2 (5 2 ·8)2 (5 2 ·9 2 ·10 2 )2 (5 3 ·8 2 ·9)2 (5 4 ·6 2 ·7 2 ·8 4 ·9 2 ·11) topology. The photodegradation studies reveal that complex1 displays highly sensitive photodegradation sensing toward methylene blue, rhodamine B, and methyl violet under UV irradiation.